Pengaruh Fraud Hexagon Terhadap Fraudulent Financial Statement pada Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2022 - Rahmah Anggeraeni; Kurnia Rina Ariani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of fraud hexagon on fraudulent financial statements. This research is classified as quantitative research. The sample of this study used financial sector companies listed on the Indonesia Stock Exchange in 2020-2022. In this study, the determination of samples was carried out using purposive sampling technique. The type of data used in this study is secondary data. The results can be concluded that external pressure, financial targets, significant effect on fraudulent financial statements, financial stability, nature of industry, ineffective monitoring, razionalization, capability, arrogance and political connection did not significantly affect the fraudulent financial statements